The Effectiveness of Compassion-Based Intervention on Parental Burnout and the Parent-Child Relationship of Mothers of Children with Separation Anxiety Disorder - Mahnaz Khosrojavid; Somayeh Mohammadi Kashka; Mozhgan Vakilian; Alireza Mohammadi Sangachin Doost; Seyyedeh Zahra Seyyed Noori (پژوهش‌های کاربردی روانشناختی, 2025)
The objective of the current study was to examine the effectiveness of compassion-based intervention on parental burnout and the parent-child relationship of mothers of children with separation anxiety disorder in Qaimshahr city for the years 2021-2022. A quasi-experimental methodology was implemented in this investigation, which included a control group and a pre-test-post-test design. Mothers of pupils diagnosed with separation anxiety disorder comprised the statistical population. The sample consisted of 30 mothers who were randomly assigned to two experimental and control groups, with 15 individuals in each group. The mothers were selected using the available sampling method and according to the research criteria. The experimental group underwent compassion training for eight 90-minute sessions, with one session scheduled each week. Conversely, the control group did not receive the intervention. Both groups were evaluated using Roskam's parental burnout scales and Pianta's parent-child relationship scales. The data was analyzed using both single and multivariate covariance analysis. The results indicated that the parent-child relationship improved in the total score and its components (including: conflict, closeness, and dependence) and the total parental burnout scores and its components (including: exhaustion in parental role, feelings of being fed up, emotional distancing, and contrast in parental) decreased following the intervention (p<0.001). Therefore, compassion can be employed as an effective intervention in this field due to its positive impact on the parent-child relationship and the reduction of mothers' burnout by inducing self-awareness and mental health.